(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background A wide variety of gingival retraction materials are available, but the efficacy of horizontal as well as vertical retraction was unknown.Purpose: The purpose of the present study was to evaluate and compare the efficiency of five different non-invasive gingival retraction systems.Materials & Method: Five different gingival retraction systems ie; Retraction cord, Retraction capsule, Racegel, Comprecap, and Traxodent retraction paste were used to retract gingiva in healthy mandibular 1st molar. After retraction impressions were made with additional silicone and cast poured with die stone, which was further sectioned along the mid buccal groove and scanned under the profile projector for measurement of vertical and horizontal separation.Result: The mean score value of traxodent paste was found to be the highest in comparison to the other four gingival retraction system. The difference between each group was found to be very highly significant(P<0.001).Conclusion: Traxodent paste was found to be the most effective and comprecap was the least effective non - invasive gingival retraction system.